Challenges to the implementation and adoption of physical distancing measures against COVID-19 by internally displaced people in Mali: a qualitative study - Ag Ahmed, Mohamed A.; Ly, Birama A.; Diarra, Niélé H.; Traore, Fatoumata B.; Diarra, Djeneba; Kande, Inna F.; Dembele, Mahamadou; Doumbia, Seydou; Alami, Hassane (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background For almost a decade now, Mali has been facing a security crisis that led to the displacement of thousands of people within the country. Since March 2020, a health crisis linked to the COVID-19 pandemic also surfaced. To overcome this health crisis, the government implemented some physical distancing measures but their adoption proved difficult, particularly among internally displaced people (IDPs). The objective of this study is to identify the challenges relating to the implementation and adoption of physical distancing measures and to determine the main mitigation measures taken by IDPs to adjust to these new policies. Methods An exploratory qualitative research was conducted in Bamako and Ségou, two of the ten regions of Mali. The study counted 68 participants including 50 IDPs, seven administrative and health authorities, and 11 humanitarian actors. Sampling was guided by the principle of saturation and diversification, and data was collected through semi-structured individual interviews (n = 36) and focus groups (n = eight). Analysis was based on thematic content analysis through NVivo software. Results The main challenges identified concerning the implementation and adoption of physical distancing measures include the proximity in which IDPs live, their beliefs and values, the lack of toilets and safe water on sites, IDPs habits and economic situation, humanitarian actors’ lack of financial resources and authority, and social pressure from religious leaders. Implemented mitigation measures include the building of new shelters or their compartmentalization, the creation of income-generating activities and food banks, psychosocial support, promoting awareness of IDPs, and nightly police patrols and surveillance to discourage IDPs from going out. Finally, a call for action is suggested for the actors involved in IDPs support and management. Conclusions The study demonstrates the difficulty for IDPs to follow most of the physical distancing measures and informs about the risk of disease spreading among IDPs with its potential consequences. It also shows the inability of mitigation measures to control the outbreak and suggests actions to be considered.